IMPLEMENTASI SUPERVISI PELAKSANAAN NEW PERTEACHING DALAM PEMBELAJARAN DI SD ISLAM AL-AZHAR 25 SEMARANG - Maula, Iffatul; NH, Khairu Ramadani; A, Faiz Abdul Majid; Bariroh, Umi; Ningsih, Rahayu (STKIP Pesisir Selatan, 2025)
The focus of the research is directed at three main aspects: the implementation of preliminary activities, core activities, and closing activities in accordance with the process standards of the Merdeka Curriculum integrated with the school’s curriculum. This research employed a qualitative descriptive approach with the subject being a Grade IV-B teacher. Data were collected through observation, structured interviews, and document analysis, and were analyzed using Miles & Huberman’s model consisting of data reduction, data display, and conclusion drawing with verification. Data validity was ensured through source and technique triangulation. The results indicate that in the preliminary stage, the teacher was able to start the lesson effectively using stimulating questions and initial assessment, although improvement is needed in connecting the material to students’ daily life experiences. In the core stage, the teacher applied active, integrative, and interactive learning steps using student-centered models, yet adaptation to individual differences among students was still limited. In the closing stage, the teacher conducted reflection and collaboratively drew conclusions with students. This study provides empirical insights into the application of new peer teaching integrated with the Merdeka Curriculum in an Islamic-based school context.